Pengaruh Tingkat Penjelajahan, Instensitas Pengunaan dan Advertisement Content Pada Instagram Terhadap Pembelian Impuls Studi Kasus: UMKM Salad Nyoo - Joseph Franz Nadeak; Admaja Dwi Herlambang; Kariyoto Kariyoto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
The development of online business today makes e-commerce (electronic commerce) evolve into s-commerce (social commerce) as a new paradigm that utilizes social media. Instagram is a Social commerce that aims for users to share photos and videos. Instagram's algorithm now helps businesses increase sales. Salad Nyoo is a company engaged in the sale of food and beverages that use instagram to market products and increase sales. In s-commerce purchases that occur not only planned purchases, but also impulsive purchases. This study aims to find out the influence of S-commerce Browsing, s-commerce Usage Intensity, Advertisement Content, Urge to Buy, and Perceived Enjoyment on Impulse Buying. The model used in this study was the S-O-R (stimulus organism response) model. Data collection techniques using purposive sampling techniques. The respondent characteristics of this study were customers of Salad Nyoo. Data processing of questionnaire results is processed using Partial Least Squares Structural Equation Model (PLS SEM). The results showed that S-commerce Usage Intensity, Advertisement Content, and Urge to buy influence Impulsive Buying in Salad Nyoo. Although one of the 6 hypotheses tested in this study, there are 3 hypotheses that are rejected, namely S-commerce Browsing against Urge to Buy, Advertisement Content against Urge to Buy and Perceived Enjoyment against Impulsive Buying.